2018
DOI: 10.1002/ncp.10201
|View full text |Cite|
|
Sign up to set email alerts
|

Bioelectrical Impedance Phase Angle and Morbidity and Mortality in Critically Ill Children

Abstract: Background Nutrition markers may be useful for diagnosis and monitoring and, also, as additional indicators of estimating death risk. We tested the association of body composition indicators (mid–upper arm circumference and phase angle) with pediatric intensive care unit (PICU) length of stay and mortality in critically ill pediatric patients. Methods Data from children aged 2 months–18 years were collected, and bioelectrical impedance was performed to obtain phase angle. Severity was evaluated by scoring the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 46 publications
1
30
0
1
Order By: Relevance
“…On average, both children with edematous SAM and wasting had lower PA than community children and low PA is reported to be associated with poor clinical outcome [28,29,48,49]. However, based on fit criteria, the models we tested did not suggest PA to contribute more than anthropometry alone towards explaining mortality, duration of hospital stay or time-to-mortality or time-todischarge.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…On average, both children with edematous SAM and wasting had lower PA than community children and low PA is reported to be associated with poor clinical outcome [28,29,48,49]. However, based on fit criteria, the models we tested did not suggest PA to contribute more than anthropometry alone towards explaining mortality, duration of hospital stay or time-to-mortality or time-todischarge.…”
Section: Discussionmentioning
confidence: 89%
“…PA reflects the phase shift between the current and voltage that results from the electrochemical membrane [25] and is associated with both cell membrane integrity, cell size, and cell mass and also with tissue resistance which depends on lean tissue and hydration status [26,27]. A low PA is associated with several diseases and higher mortality risk [13] and the use of clinical cut-off values have been suggested to identify children at risk of poor health outcome [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…We read with interest the recent study of bioelectrical impedance analysis (BIA) in critically ill children, in which the authors report a challenge to conform with 1 of the standard BIA conditions (side of electrode placement).…”
Section: Adherence To Standard Bia Conditions Among Oncology and Rheumentioning
confidence: 99%
“…Challenges with standard BIA conditions, as acknowledged by Zamberlan et al, are rarely reported. Some have used non‐standard BIA conditions, with patients asked to stand during BIA measurement.…”
Section: Adherence To Standard Bia Conditions Among Oncology and Rheumentioning
confidence: 99%
“…Thus, BIA does not seem to be a good method to evaluate body composition in cases where these 2 principles are not valid, such as critically ill patients who usually present with hydration disorders, since the amount of total body water interferes in FFM and fat mass estimation. Taking this into account, the aim of our study was not to use the body composition estimation by BIA but rather the PA whose measurement indirectly reflects the FFM, and it is not subjected to prediction equations and it is not influenced by hydration. Thus, to avoid the hydration bias in FFM, we did not use the body compartments estimation by BIA, and we just considered the PA values.…”
mentioning
confidence: 99%